Laparoscopic treatment of symptomatic simple renal cysts in children: single-center experience - Antonio Marte; Lucia Pintozzi (PAGEPress Publications, 2018)
Simple renal cysts, although common in adults, are rare in children. They are usually discovered incidentally in the course of the study of other urinary tract symptoms, although they are not always asymptomatic. Renal cysts can be classified as being either simple or complex. The purpose of this review is to present our case series of simple symptomatic renal cysts treated with laparoscopy. Nineteen patients with symptomatic renal cysts (6 to 13.5 cm) were referred to our institution between January 2006 and January 2017. They comprised 12 (40.5%) females and seven (59.5%) males, aged 8 to 15, with a mean age of 12.2 years. Of these patients, nine had previously been treated unsuccessfully by ultrasound-guided aspiration/alcoholization with 95%-ethanol, between 9 and 13 months prior to the laparoscopy. Five patients had undergone one treatment and four had undergone two treatments. All of the patients were treated by laparoscopic threetrocar deroofing. The cysts were opened and the wall excised using scissors and a monopolar hook. In most cases, to better handle the edges of the cyst and obtain a better grip, a needle was used to aspirate a small amount of fluid (used for cytological examination). The wall of the cyst was excised, the cyst edges were sealed, and the perirenal fat was placed on the bottom of the cyst (wadding technique). The mean operating time was 95 minutes (range 50- 150). The postoperative course was uneventful for all of the patients. The hospital stay ranged from one to three days. All of the patients were asymptomatic following the treatment. At a mean follow-up time of 3.6 years, none of the patients had experienced a recurrence. Renal function, as assessed by a MAG3 renal scintigraphy scan, was well-preserved in all of the patients, and all of them undergo an annual ultrasound scan.